Impact of prostate edema on cell survival and tumor control after permanent interstitial brachytherapy for early stage prostate cancers - Chen, Zhe (Jay) (2011)
Previous studies have shown that the procedure-induced prostate edema during permanent interstitial brachytherapy (PIB) can cause significant variations in the dose delivered to the prostate gland. Because the clinical impact of edema-induced dose variations depends strongly on the magnitude of the edema, the temporal pattern of its resolution and its interplay with the decay of radioactivity and the underlying biological processes of tumor cells (such as tumor potential doubling time), we investigated the impact of edema-induced dose variations on the tumor cell survival and tumor control probability after PIB with the (131)Cs, (125)I and (103)Pd sources used in current clinical practice. The exponential edema resolution model reported by Waterman et al. (Int. J. Radiat. Oncol. Biol. Phys. 41, 1069–1077–1998) was used to characterize the edema evolutions observed previously during clinical PIB for prostate cancer. The concept of biologically effective dose (BED), taking into account tumor cell proliferation and sublethal damage repair during dose delivery, was used to characterize the effects of prostate edema on cell survival and tumor control probability. Our calculation indicated that prostate edema, if not taken into account appropriately, can increase the cell survival and decrease the probability of local control of PIB. The edema-induced increase in cell survival increased with increasing edema severity, decreasing half-life for radioactive decay and decreasing energy of the photons energy emitted by the source. At the doses currently prescribed for PIB and for prostate cancer cells characterized by nominal radiobiology parameters recommended by AAPM TG-137, PIB using (125)I sources was less affected by edema than PIB using (131)Cs or (103)Pd sources due to the long radioactive decay half-life of (125)I. The effect of edema on PIB using (131)Cs or (103)Pd was similar. The effect of edema on (103)Pd PIB was slightly greater, even though the decay half-life of (103)Pd (17 days) is longer than that of (131)Cs (9.7 days), because the advantage of the longer (103)Pd decay half-life was negated by the lower effective energy of the photons it emits (~21 keV compared to ~30.4 keV for (131)Cs). In addition, the impact of edema could be reduced or enhanced by differences in the tumor characteristics (e.g. potential tumor doubling time or the α/β ratio), and the effect of these factors varied for the different radioactive sources. There is a clear need to consider the effects of prostate edema during the planning and evaluation of permanent interstitial brachytherapy treatments for prostate cancer.